Perancangan Data Warehouse Untuk Mendukung Keputusan Strategi Pemasaran Dalam Penjualan - Nova Magdalena Br Hombing; Welmi Simanjuntak; Andri Wijaya (Journal Of Informatics And Busisnes, 2025)
Operational sales data is often fragmented, impeding management from developing data driven marketing strategies. This research aims to conceptually design a data warehouse to support sales marketing strategy decision making. The method utilizes a descriptive-conceptual approach employing the Kimball’s Nine-Step methodology on the Superstore Sales Data (2025) dataset from Kaggle. The resulting design is a Star Schema, which integrates historical data (customer, product, region, and time). Via the ETL (Extract, Transform, Load). The derived multidimensional analysis yields critical insights: Furniture products are the primary profit drivers, the Home Office segment demonstrates superior profitability, and the Q4 seasonal pattern (October-December) is the consistent sales speak. This data warehouse model proves effective in providing structured, actionable insights for marketing profit optimization.